2021
DOI: 10.1016/j.amsu.2021.102468
|View full text |Cite
|
Sign up to set email alerts
|

Post-intubation tracheal stenosis after severe COVID-19 infection: A report of two cases

Abstract: Introduction and importance Coronavirus disease 2019 (COVID-19) is a pandemic disease that spread rapidly throughout the world and became a major public health concern. Approximately 5–12% of COVID-19 patients require admission to the intensive-care unit (ICU), where they often require oxygen therapy and prolonged intubation. Post-intubation laryngotracheal stenosis (PILS) is a complication that occurs in 10–22% of non-COVID-19 patients after prolonged intubation, while the rate of COVID-19 relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 8 publications
1
21
0
3
Order By: Relevance
“…The true incidence of PITS might be even higher as a number of post-COVID patients may not be referred for dyspnea/tracheal stenosis due to more debilitating COVID-related post-ICU sequelae. Other authors have also observed a similar increase in the incidence of these complications, which could either be attributed to the dramatic increase of intubated patients due to the pandemic or to other factors related to specific patients’ characteristics, to the disease itself, or ultimately to iatrogenic factors related with the hospitalization and the disease management under the current circumstances [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The true incidence of PITS might be even higher as a number of post-COVID patients may not be referred for dyspnea/tracheal stenosis due to more debilitating COVID-related post-ICU sequelae. Other authors have also observed a similar increase in the incidence of these complications, which could either be attributed to the dramatic increase of intubated patients due to the pandemic or to other factors related to specific patients’ characteristics, to the disease itself, or ultimately to iatrogenic factors related with the hospitalization and the disease management under the current circumstances [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 75%
“…In a number of case reports, it was highlighted that common post-COVID-19 respiratory symptoms, such as cough and dyspnea after discharge from the hospital, were initially misdiagnosed and later attributed to post-intubation tracheal stenosis [ 27 ]. Prolonged intubation and prone position MV combined with obesity and diabetes have again been recognized as predisposing factors for the development of post-intubation tracheal stenosis in several small case series [ 28 , 29 , 30 , 31 ]. However, Fiacchini G. et al [ 32 ] compared patients with and without COVID-19, all of whom had undergone prolonged (>14 days) MV.…”
Section: Discussionmentioning
confidence: 99%
“…Many papers related to acute and late laryngotracheal complications in COVID-19 patients subjected to invasive mechanical ventilation have been published in the last few months ( Alturk et al, 2021 ; Balakrishnan et al, 2021 ; Fiacchini et al, 2021 ; Mahmood et al, 2021 ; Sandu, 2021 ; Scholfield et al, 2021 ). In order to explain the increase in the incidence of this particular type of complication, several etiopathogenetic hypotheses have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Post-intubation LTS is rare with an estimated 4.9 cases per one million individuals per year in the general population [8] . Up to 5 % of non-pregnant adults with COVID-19 infection who required invasive ventilation developed symptomatic post-intubation LTS [9] .…”
Section: Discussionmentioning
confidence: 99%